Inside Cover: Consolidating Molecular Logic with New Solid‐Bound YES and PASS 1 Gates and Their Combinations (ChemPhysChem 13/2017). Issue 13 (26th June 2017) - McKinney, Bernadine O. F.; Daly, Brian; Yao, Chaoyi; Schroeder, Marc; de Silva, A. Prasanna
Abstract : The Inside Cover picture illustrates how the worldwide growth of molecular logic is being consolidated by parallel integration of gates on solid particles to facilitate the molecular computational identification (MCID) of these micrometric objects. Picture courtesy of Ziwei Liu and Zeqing Chen. More information can be found in the Full Paper by A. P. de Silva and co‐workers onpage 1760 in Issue 13, 2017 (DOI:10.1002/cphc.201700120 ).